Copper foil and laminates and methods for manufacturing the same

KR103035552B1Active Publication Date: 2026-10-21NAMICS CORPORATION
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
KR1020237004411
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-09-07
Filing Date
2021-08-06
Publication Date
2026-10-21
Estimated Expiration
2041-08-06

Smart Images

  • Figure 112023014135261-PCT00007_ABST
    Figure 112023014135261-PCT00007_ABST
Patent Text Reader

Abstract

The present invention aims to provide a copper foil that, when a wiring board is manufactured using a resin substrate made of LCP, can obtain a wiring board capable of having high-frequency characteristics and high peel strength. The copper foil has irregularities on some or all of its surface, and the Ra of the irregularities is 0.01 μm or more and 0.10 μm or less, and the RSm is 1.20 μm or more and 4.00 μm or less, or the Rz is 0.1 μm or more and 0.90 μm or less, and the RSm is 1.20 μm or more and 4.00 μm or less, or the Ra is 0.034 μm or more and 0.092 μm or less, and the Rz is 0.25 μm or more and 0.87 μm or less, and the RSm is 1.21 μm or more and 3.57 μm or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to copper foil and laminates and methods for manufacturing the same. Background Technology

[0002] The demand for liquid crystal polymers (LCPs) is increasing, particularly for high-speed transmission and precision components in the electrical and electronic and information and communication fields. This is believed to be due to the fact that LCPs possess characteristics such as high heat resistance, low water absorption, minimal dimensional change due to humidity, and excellent electrical properties. To achieve high adhesion with copper foil, methods such as using rough copper foil or surface modification of LCPs by UV irradiation or plasma treatment are being performed (Japanese Patent Publication No. 2003-221456, Japanese Patent Publication No. 2008-103559, Japanese Patent Publication No. 2012-140552). The problem to be solved

[0003] The present invention aims to provide a copper foil that enables the production of a wiring board having good high-frequency characteristics and high peel strength when the wiring board is manufactured using a resin substrate made of LCP. means of solving the problem

[0004] As a result of diligent research to obtain a copper foil having high adhesion to LCP, the inventors of the present invention discovered that high adhesion to LCP can be achieved by forming irregularities of a specific shape on the surface of the copper foil, thereby completing the present invention.

[0005] The embodiments of the present invention are as follows.

[0006] (1) A copper foil having irregularities on some or all of its surface, wherein the Ra of the irregularities is 0.01 μm or more and 0.10 μm or less, and the RSm is 1.20 μm or more and 4.00 μm or less.

[0007] (2) A copper foil having irregularities on some or all of its surface, wherein the Rz of the irregularities is 0.2 μm or more and 0.90 μm or less, and the RSm is 1.20 μm or more and 4.00 μm or less.

[0008] (3) A copper foil described in claim 1 or 2, wherein the Ra of the above irregularities is 0.034 μm or more and 0.092 μm or less, and the Rz is 0.25 μm or more and 0.87 μm or less, and the RSm is 1.21 μm or more and 3.57 μm or less.

[0009] (4) A copper foil described in any one of claims 1 to 3, wherein the area ratio of the binarized convex portion is 42% or more and 90% or less in a binarized image with a grayscale value of 120 as the threshold value in a grayscale image of the above surface at a magnification of 50,000x by a scanning electron microscope (SEM).

[0010] (5) A copper foil described in claim 4, in which the area ratio of the binarized convex portion is 58% or more and 81% or less in a binarized image with a grayscale value of 120 as the threshold value in a grayscale image of the surface at a magnification of 50,000x by a scanning electron microscope (SEM).

[0011] (6) A copper foil described in claim 4, in which the area ratio of the binarized convex portion is 58% or more and 73% or less in a grayscale image of the surface at a magnification of 50,000x using a scanning electron microscope (SEM) with a grayscale value of 120 as the threshold value.

[0012] (7) A copper foil described in any one of claims 1 to 6, wherein, in an image taken by a scanning electron microscope (SEM) of a cross-section perpendicular to the surface, a straight line parallel to the surface of the copper foil is drawn from the highest and lowest points of the irregularities, and each is designated as Level 1 and Level 0, and the number of intersection points between the straight line of Level 0.5 and the contour of the surface is 5 or more and 50 or less per any 2.3 μm.

[0013] (8) A copper foil according to claim 7, in which, in an image by scanning electron microscope (SEM) of a cross-section perpendicular to the surface, straight lines parallel to the surface of the copper foil are drawn from the highest and lowest points of the irregularities, and each is designated as Level 1 and Level 0, respectively, and the number of intersection points between the straight line of Level 0.5 and the contour of the surface is 10 or more and 20 or less per any 2.3 μm.

[0014] (9) A copper foil described in any one of claims 1 to 8, wherein a first layer containing copper oxide is present on part or all of the surface of the copper foil.

[0015] (10) Copper foil described in claim 9, having a second layer containing a metal other than copper on the surface of the first layer.

[0016] (11) Copper foil described in item 10, the second layer being a plated film.

[0017] (12) Copper foil described in claim 10 or 11, wherein the metal other than copper comprises nickel.

[0018] (13) The average adhesion amount of the second layer is 0.8~6.0 mg / dm 2 Copper foil described in any one of paragraphs 10 to 12.

[0019] (14) A laminate in which a copper foil described in any one of claims 1 to 13 is laminated on a resin substrate.

[0020] (15) A laminate in which a copper foil is laminated on a resin substrate, wherein, in an image taken by a scanning electron microscope (SEM) of a cross-section perpendicular to the interface between the resin substrate and the copper foil, a straight line parallel to the interface is drawn from the highest and lowest points of the irregularities present at the interface and is designated as Level 1 and Level 0, respectively, and the number of intersection points between the straight line of Level 0.5 and the irregularities is 5 or more and 50 or less per any 2.3 μm.

[0021] (16) A laminate described in claim 15, wherein the number of the above intersection points is 10 or more and 20 or less per any 2.3 μm.

[0022] (17) A laminate according to any one of claims 14 to 16, wherein the copper foil comprises the copper foil described in any one of claims 1 to 14.

[0023] (18) Electronic components mounted on copper foil as described in any one of paragraphs 1 through 13.

[0024] (19) An electronic component mounted on a laminate as described in any one of paragraphs 14 through 17.

[0025] (20) A method for manufacturing copper foil as described in any one of claims 1 to 13, comprising a first step of forming the above irregularities by treating the copper foil that serves as the material with an oxidizing agent, wherein the oxidizing agent contains 20 g / L or more and 160 g / L or less of hydroxide.

[0026] (21) A method for manufacturing copper foil as described in claim 20, wherein the above hydroxide is sodium hydroxide, potassium hydroxide, or a combination thereof.

[0027] (22) The above oxidizing agent contains 60 g / L or less of hypochlorite, a method for producing copper foil as described in claim 20 or 21.

[0028] (23) The above chlorite is sodium chlorite, potassium chlorite, or a combination thereof, a method for manufacturing copper foil as described in paragraph 22.

[0029] (24) A method for manufacturing copper foil as described in claim 22 or 23, wherein the ratio of the content of the hypochlorite to the content of the hydroxide is greater than 0 and less than or equal to 1.0.

[0030] (25) A method for manufacturing copper foil as described in any one of claims 20 to 24, comprising a second process of treating the copper foil that is the material with an alkaline solution with a pH of 9 or higher, which is performed before the first process.

[0031] (26) A method for manufacturing copper foil as described in any one of claims 20 to 25, comprising a third process of treating the copper foil with a solvent, which is performed after the first process.

[0032] (27) A method for manufacturing copper foil as described in any one of claims 20 to 26, comprising a fourth process of treating the copper foil with a reducing agent, which is performed after the first process.

[0033] (28) A method for manufacturing copper foil as described in any one of claims 20 to 27, comprising a fifth process of plating the copper foil, which is performed after the first process.

[0034] (29) A method for manufacturing copper foil as described in any one of claims 20 to 28, comprising a sixth process of treating the copper foil with a coupling agent, which is performed after the first process.

[0035] (30) A method for manufacturing a laminate comprising a process of laminating a copper foil described in any one of claims 1 to 13 onto a resin substrate.

[0036] (31) A method for manufacturing a laminate as described in claim 30, wherein the resin substrate contains a liquid crystal polymer (LCP).

[0037] ==Cross-reference with related literature==

[0038] This application claims priority based on Japanese patent application No. 2020-150136 filed on September 7, 2020, and incorporates said basic application by citing it. Brief explanation of the drawing

[0039] Figure 1 is a scanning electron microscope (SEM) image of the copper foil surface in a representative embodiment and a comparative example of the present invention. Figure 2 is an image of the copper foil surface of an embodiment of the present invention before and after binarization using a scanning electron microscope (SEM). FIG. 3 is a diagram illustrating a method in which, in one embodiment of the present invention, a scanning electron microscope (SEM) image of a cross-section perpendicular to the surface of a copper foil is used to draw a straight line parallel to the surface of the copper foil from the highest and lowest points of the irregularities present on the surface of the copper foil, designating them as Level 1 and Level 0 respectively (A), a straight line of Level 0.5 is drawn (B), and the number of intersection points between the straight line of Level 0.5 and the irregularities is counted (C). Specific details for implementing the invention

[0040] Hereinafter, preferred embodiments of the present invention will be described in detail with reference to the accompanying drawings, but are not limited thereto. Furthermore, the purpose, features, advantages, and ideas of the present invention are obvious to those skilled in the art from the description in this specification, and those skilled in the art can easily reproduce the present invention from the description in this specification. The embodiments and specific examples of the invention described below represent preferred embodiments of the present invention and are provided for illustrative or explanatory purposes only and are not intended to limit the present invention. It is obvious to those skilled in the art that various modifications and variations are possible based on the description in this specification within the intent and scope of the present invention as disclosed herein.

[0041] Copper foil

[0042] One embodiment of the present invention is a copper foil having irregularities on a part or all of its surface. The RSm of the irregularities is preferably 1.20 or higher, more preferably 1.21 or higher, even more preferably 1.50 or higher, and also preferably 5.00 or lower, more preferably 4.00 or lower, even more preferably 3.57 or lower, and even more preferably 3.00 or lower. The Ra of the irregularities is preferably 0.005 or higher, more preferably 0.01 or higher, even more preferably 0.034 or higher, even more preferably 0.05 or higher, and also preferably 0.20 or lower, more preferably 0.10 or lower, even more preferably 0.092 or lower, and even more preferably 0.07 or lower. It is preferable that the Rz of the irregularity be 0.1 or higher, more preferable that it be 0.2 or higher, even more preferable that it be 0.25 or higher, even more preferable that it be 0.30 or higher, and also preferable that it be 1.00 or lower, more preferable that it be 0.90 or lower, even more preferable that it be 0.87 or lower, and even more preferable that it be 0.8 or lower. As a combination of numerical values, it is preferable that Ra be 0.01 or higher and 0.10 or lower and RSm be 1.20 or higher and 4.00 or lower, or that Rz be 0.2 or higher and 0.90 or lower while RSm is 1.20 or higher and 4.00 or lower. Additionally, it is preferable that Ra be 0.034 or higher and 0.092 or lower and Rz be 0.25 or higher and 0.87 or lower while RSm is 1.21 or higher and 3.57 or lower.

[0043] In addition, RSm represents the average of the length of one cycle of irregularities (i.e., the length of the contour curve element: Xs1~Xsm) included in the roughness curve at a certain reference length (lr), and is calculated by the following formula.

[0044] Equation 1

[0045]

[0046] Here, 10% of the arithmetic mean roughness (Ra) is set as the minimum height of the irregularity, and 1% of the reference length (lr) is set as the minimum length to define one cycle of irregularity.

[0047] Arithmetic mean roughness (Ra) represents the average of the absolute values ​​of Z(x) (i.e., mountain heights and valley depths) in a contour curve (y=Z(x)) expressed by the following formula, at a reference length l.

[0048] Equation 2

[0049]

[0050] As an example, RSm can be calculated by 'creating a contour curve from the results of observation by a confocal microscope (JIS B 0601:2001)'.

[0051] In addition, Rz (maximum height) represents the sum of the maximum peak height Zp and the maximum valley depth Zv of the contour curve (y=Z(x)) at a reference length l, and Ra (arithmetic mean roughness) represents the average of the absolute values ​​of Z(x) (i.e., peak height and valley depth) in the contour curve (y=Z(x)) at a reference length l. These Rz and Ra can be calculated by the method specified in JIS B 0601:2001 (in accordance with the international standard ISO 13565-1).

[0052] The copper foil may include tough pitch copper, deoxidized copper, and oxygen-free copper, or may be composed of tough pitch copper, deoxidized copper, and oxygen-free copper, but it is more preferable that it be oxygen-free copper with an oxygen content of 0.0005 mass% or less.

[0053] The copper foil may be a single sheet of copper foil, such as electrolytic copper foil or rolled copper foil, or multiple sheets of copper foil may be laminated. The thickness of the copper foil is not particularly limited, but is preferably 0.1 μm or more and 100 μm or less, and more preferably 0.5 μm or more and 50 μm or less.

[0054] In a grayscale image of the surface of a copper foil at a magnification of 50,000x obtained by a scanning electron microscope (SEM), in a binarized image with a grayscale value of 120 as the threshold, it is preferable that the area ratio of the convex portion is 40% or more, more preferable that it is 42% or more, more preferable that it is 58% or more, more preferable that it is 60% or more, and also preferable that it is 95% or less, more preferable that it is 90% or less, more preferable that it is 81% or less, more preferable that it is 73% or less, and more preferable that it is 70% or less. As a combination of numerical values, it is preferable that it is 42% or more and 90% or less, more preferable that it is 58% or more and 81% or less, and more preferable that it is 58% or more and 73% or less.

[0055] In addition, in an image of a cross-section perpendicular to the surface of the copper foil at a magnification of 50,000x obtained by a scanning electron microscope (SEM), straight lines parallel to the surface of the copper foil are drawn from the highest and lowest points of the irregularities and designated as Level 1 and Level 0, respectively. It is preferable that the number of intersection points between the straight line of Level 0.5 and the contour of the surface is 3 or more per any 2.3 μm, more preferable that it is 5 or more, and even more preferable that it is 10 or more. Furthermore, it is preferable that it is 50 or less, more preferable that it is 20 or less, and even more preferable that it is 13 or less. As for a combination of numbers, it is preferable that it is 5 or more and 50 or less per any 2.3 μm, and more preferable that it is 10 or more and 20 or less.

[0056] A first layer containing copper oxide may exist on part or all of the surface of the copper foil, or on part or all of the back surface. This copper oxide contains copper oxide (CuO) and / or cuprous oxide (Cu2O). This layer containing copper oxide can be formed by oxidizing the surface of the copper foil. Through this oxidation treatment, the surface of the copper foil is roughened. After the oxidation treatment, the shape of the convexities on the oxidized conductor surface may be adjusted using a solvent. Additionally, the surface of this layer containing copper oxide may be reduced using a reducing agent. The resistivity of pure copper is 1.7 × 10⁻⁶ -8 While it is (Ωm), copper oxide is 1–10 (Ωm), and cuprous oxide is 1×10 6 ~1×10 7 Because (Ωm), the conductivity of the layer containing copper oxide formed by oxidation treatment is lower than that of pure copper.

[0057] A second layer containing a metal other than copper may be present on the surface of the first layer of the copper foil. The second layer may be composed of a metal other than copper. The metal included in the second layer is not particularly limited, but may include at least one metal selected from the group consisting of Sn, Ag, Zn, Al, Ti, Bi, Cr, Fe, Co, Ni, Pd, Au, and Pt. In particular, to impart acid resistance and heat resistance, it is preferable to include a metal with higher acid resistance and heat resistance than copper, such as Ni, Pd, Au, and Pt.

[0058] The adhesion amount of the second layer is not particularly limited, but is 0.8–6.0 mg / dm² 2 It is desirable that... In addition, the amount of the second layer attached is a value calculated by dissolving the second layer, for example, in an acidic solution, measuring the amount of metal by ICP analysis, and dividing it by the planar viewing area of ​​the structure.

[0059] Laminated structure

[0060] A laminate can be constructed by using copper foil together with an insulator. The copper foil described above can be used. This laminate is called a copper clad laminate (CCL) and can be used as a substrate for printed circuit boards.

[0061] The insulator may include a sheet-type resin substrate impregnated with resin, or may consist of a sheet-type resin substrate impregnated with resin. The laminate may be manufactured by attaching copper foil to one or both sides of the insulator. The laminate may be a three-layer structure (i.e., metal layer, adhesive layer, and resin layer) in which copper foil and a resin substrate are bonded using an adhesive, which is mainly used for tape-automated bonding (TAB) mounting, or a two-layer structure (i.e., metal layer and resin layer) in which no adhesive is used, which is used for chip-on-film (COF) mounting. Additionally, as an insulator, a resin substrate may be superimposed on a substrate such as paper or glass and heat-pressed, in which case a copper foil is attached to the opposite side of the substrate.

[0062] The resin included in the resin substrate is not particularly limited, but may be a thermoplastic resin or a thermosetting resin, and is preferably polyphenylene ether (PPE), epoxy, polyphenylene oxide (PPO), polybenzoxazole (PBO), polytetrafluoroethylene (PTFE), liquid crystal polymer (LCP), triphenylphosphite (TPPI), fluoropolymer, polyetherimide, polyether ether ketone, polycycloolefin, bismaleimide resin, low dielectric constant polyimide, cyanate resin, or a mixture thereof. The resin substrate may also include inorganic fillers or glass fibers. The thickness of the resin substrate is not particularly limited, but is preferably 1 μm or more and 100 mm or less.

[0063] In a scanning electron microscope (SEM) image at a magnification of 50,000x of a cross-section perpendicular to the interface between the resin substrate and the copper foil, straight lines parallel to the interface are drawn from the highest and lowest points of the irregularities present at the interface and designated as Level 1 and Level 0, respectively. It is preferable that the number of intersection points between the straight line of Level 0.5 and the contour of the surface is 3 or more per any 2.3 μm, more preferable that it is 5 or more, and even more preferable that it is 10 or more. Furthermore, it is preferable that it is 50 or less, more preferable that it is 20 or less, and even more preferable that it is 13 or less. In terms of numerical combinations, it is preferable that it is 5 or more and 50 or less per any 2.3 μm, and more preferable that it is 10 or more and 20 or less. Additionally, the surface shape of the copper foil may change before and after lamination with the resin substrate, but it is preferable that it does not change significantly.

[0064] Method for manufacturing copper foil

[0065] One embodiment of the present invention is a method for manufacturing any copper foil described above, comprising one or more processes selected from a first process of forming a first layer containing copper oxide on the surface of part or all of the copper foil, a second process of forming a second layer containing a metal other than copper on the surface of the first layer, and a third process of coupling the surface of the second layer. When performing multiple processes, it is preferable to perform the process with the larger number later, such as performing the second process after the first process, but it is most preferable to perform the three processes in this order.

[0066] First, as a first process, the surface of the copper foil may be oxidized with an oxidizing agent to form a layer containing copper oxide, while simultaneously forming fine irregularities on the surface. The oxidation treatment may be a single-sided treatment or a double-sided treatment. The first process may include a surface roughening treatment process, such as soft etching or etching, performed prior to this oxidation process. Additionally, the first process may include a degreasing treatment process performed prior to the oxidation treatment, an acid cleaning process to homogenize the surface by removing an oxide film present on the copper foil serving as the material, and an alkali treatment process to prevent the introduction of acid into the oxidation process after acid cleaning. The alkali treatment method is not particularly limited, but preferably, it is sufficient to treat with an alkali aqueous solution of 0.1 to 10 g / L, more preferably 1 to 2 g / L, for example, an aqueous sodium hydroxide solution, at 30 to 50°C for about 0.5 to 2 minutes.

[0067] The oxidizing agent used in the first process preferably contains a hydroxide or is composed of a hydroxide. Examples of hydroxides include sodium hydroxide and potassium hydroxide. In this case, the total concentration of the hydroxide is 20 g / L or higher and 160 g / L or lower. Additionally, the oxidizing agent may contain a hydroxide and a chlorite, or be composed of a hydroxide and a chlorite. Examples of chlorites include sodium hypochlorite and potassium hypochlorite. In this case, the total concentration of the chlorite is higher than 0 g / L and is 60 g / L or lower. Furthermore, the oxidizing agent may contain 3-glycidyloxypropyltrimethoxysilane (3-GT). In this case, the concentration of 3-glycidyloxypropyltrimethoxysilane may be higher than 0 g / L and may be 10 g / L or lower; it is preferably 5 g / L or lower, and more preferably 1 g / L or lower. In summary, it is preferable that the oxidizing agent contains 20 to 160 g / L of hydroxide, 0 to 60 g / L of hypochlorite, and 0 to 10 g / L of 3-glycidyloxypropyltrimethoxysilane, or is composed of these. Additionally, it is preferable that the ratio of the hypochlorite content to the hydroxide content be 0 or greater and 1.0 or less. These elements are particularly important for the manufacture of the copper foil of the present disclosure.

[0068] Various additives (e.g., phosphates such as trisodium phosphate douhydrate) or surface-active molecules may also be added to the oxidizing agent. As surface-active molecules, porphyrin, porphyrin macrocircle, extended porphyrin, ring-reduced porphyrin, linear porphyrin polymer, porphyrin sandwich coordination complex, porphyrin arrangement, silane, tetraorgano-silane, aminoethyl-aminopropyl-trimethoxysilane, (3-aminopropyl)trimethoxysilane, (1-[3-(trimethoxysilyl)propyl]urea)((l-[3-(Trimethoxysilyl)propyl]urea)), (3-aminopropyl)triethoxysilane, ((3-glycidyloxypropyl)trimethoxysilane), (3-chloropropyl)trimethoxysilane, (3-glycidyloxypropyl)trimethoxysilane, dimethyldichlorosilane, 3-(trimethoxysilyl)propyl methacrylate, ethyltriacetoxysilane, Examples include triethoxy(isobutyl)silane, triethoxy(octyl)silane, tris(2-methoxyethoxy)(vinyl)silane, chlorotrimethylsilane, methyltrichlorosilane, silicon tetrachloride, tetraethoxysilane, phenyltrimethoxysilane, chlorotriethoxysilane, ethylene-trimethoxysilane, amines, sugars, etc.

[0069] The oxidation reaction conditions are not particularly limited, but the liquid temperature of the oxidizing agent is preferably 40 to 95°C, and more preferably 45 to 80°C. The reaction time is preferably 0.5 to 30 minutes, and more preferably 1 to 10 minutes.

[0070] Before performing the first process, surface roughening treatments such as soft etching or etching are not required, but may be performed. Additionally, before the oxidation treatment, a second process may be performed, which includes degreasing, acid washing to homogenize the surface by removing the natural oxide film, or alkali treatment to prevent acid from entering the oxidation process after acid washing. The method of alkali treatment is not particularly limited, but preferably, it is sufficient to treat with an alkali aqueous solution of 0.1 to 10 g / L, more preferably 1 to 2 g / L, for example, an aqueous sodium hydroxide solution, at 30 to 50°C for about 0.5 to 2 minutes. It is preferable that the alkali aqueous solution has a pH of 9 or higher or a pH of 10 or higher.

[0071] After the first process, a third process may be performed to treat a layer containing copper foil, particularly copper oxide, with a solvent.

[0072] The solvent used in this third process is not particularly limited, but a chelating agent may be an example. It is particularly preferred that it be a biodegradable chelating agent, and examples may include ethylenediamine tetraacetic acid, diethanol glycine, L-glutamic acid diacetic acid tetrasodium, ethylenediamine-N,N'-disuccinic acid, 3-hydroxy-2,2'-iminodisuccinate sodium, methylglycine diacetic acid trisodium, aspartate diacetic acid tetrasodium, N-(2-hydroxyethyl)iminodiacetic acid disodium, sodium gluconate, etc.

[0073] The pH of the solution of the solvent is not particularly limited, but it is preferable that it be alkaline, more preferable that it be pH 8 to 10.5, even more preferable that it be pH 9.0 to 10.5, and even more preferable that it be pH 9.8 to 10.2.

[0074] In addition, a fourth process may be performed after the first process or after the third process to treat the copper oxide contained in the first layer with a reducing agent. Examples of reducing agents used in this fourth process include dimethylamineborane (DMAB), diborane, sodium borohydride, and hydrazine.

[0075] Next, a fifth process of forming a second layer on the copper foil having formed the first layer may be performed after the first process, or after the third or fourth process. The second conductor layer can be formed as a plating film, for example, by plating the surface of the first conductor layer. The method of plating is not particularly limited and examples include electrolytic plating, electroless plating, chemical treatment, vacuum deposition such as sputtering, etc., but electrolytic plating is preferred because it is desirable to form a uniform and thin plating film.

[0076] When forming a second layer by electroplating on the surface of a copper foil having a first layer containing copper oxide, the copper oxide on the surface is first reduced to cuprous oxide or pure copper, and since charge is used for this process, a time lag occurs until plating is completed, after which the metal forming the second layer begins to precipitate. Although the amount of charge varies depending on the type of plating solution and the amount of copper oxide, for example, when performing Ni plating on a copper component, in order to ensure the thickness falls within a desirable range, the area dm of the copper component undergoing electroplating must 2 It is preferable to apply a charge of 15 C or more and 75 C or less, and it is more preferable to apply a charge of 25 C or more and 65 C or less. Through plating treatment, some or all of the copper oxide formed by oxidation treatment is reduced to copper, and as the conductivity of the layer containing copper oxide increases, electrical conduction between the copper foil and the second layer becomes easier.

[0077] The method for confirming whether conductivity is present is not particularly limited, but for example, the planar viewing area of ​​the second layer is 4 μm 2 Regarding this, when a voltage of -0.5 V is applied between the copper foil and the second layer, in the current image of the atomic force microscope (AFM), if the region where the current value is -60 nA or less is 2.5% or more, 5% or more, or 10% or more of the planar field of view of the second layer, it can be determined that conductivity is being achieved between the copper foil and the second layer. Alternatively, when a substrate for a printed circuit board is manufactured using a laminate, if electronic components are mounted on the second layer and function as an electrical circuit, it can be determined that conductivity is being achieved between the copper foil and the second layer.

[0078] Next, a sixth process including a coupling treatment using a silane coupling agent on the surface of the second layer may be performed after the first process or after the third, fourth, or fifth process. By doing so, stronger adhesion to the resin substrate can be imparted to the surface of the second layer. This is described in detail in Japanese Patent Application No. 2019-236800, and the entire contents thereof are incorporated into this specification by citing said specification.

[0079] As for the silane coupling agent used, it is preferable that the hydrolyzable group has 2 or 3 groups, and it is preferable that the hydrolyzable group is a methoxy group or an ethoxy group.

[0080] Although not specifically limited, 3-mercaptopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, vinyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane, 3-ureidpropyltrialkoxysilane, 3-acryloxypropyltrimethoxysilane, etc. may be used.

[0081] In the sixth step, specifically, a solution in which a silane coupling agent is dispersed in water or an organic solvent is applied or sprayed onto the surface of the second layer to adsorb the mixture, and then dried. The solution in which the silane coupling agent is dispersed in water or an organic solvent is not particularly limited, but it is preferable to have a weight percentage of 0.5% or more, 1% or more, 2% or more, 4% or more, or 8% or more, and 20% or less, 15% or less, or 10% or less. The drying temperature and time are not particularly limited as long as the solvent, water or organic solvent, is completely evaporated, but it is preferable to dry at 70°C for 1 minute or more, more preferable to dry at 100°C for 1 minute or more, and even more preferable to dry at 110°C for 1 minute or more.

[0082] Method for manufacturing a laminate

[0083] Next, an insulator is laminated onto the surface of the copper foil treated as described above. If the insulator includes a resin substrate or is made of a resin substrate, for example, the insulating layer can be laminated by heat-pressing the resin substrate onto the conductor foil. The heat-pressing conditions may utilize the recommended conditions of each substrate manufacturer (e.g., temperature, pressure, time).

[0084] The resin substrate is not particularly limited, but it is preferable to include a liquid crystal polymer (LCP) or to be composed of an LCP. Known LCPs, including commercially available products, may be used; examples include polycondensates of ethylene terephthalate and parahydroxybenzoic acid, polycondensates of phenol and phthalic acid and parahydroxybenzoic acid, and polycondensates of 2,6-hydroxynaphthoic acid and parahydroxybenzoic acid. In particular, a thermotropic liquid crystal polymer is preferred.

[0085] Method for manufacturing printed circuit boards

[0086] Using the laminate manufactured in this way, a Printed Wiring Board (PWB) can be manufactured, and a Printed Circuit Board (PCB) can also be manufactured by soldering electronic components.

[0087] A wiring board using the copper foil or laminate of the present disclosure can preferably be used as a high-frequency circuit board.

[0088] Examples

[0089] (1) Treatment of copper foil

[0090] The copper foil used in the examples and comparative examples and its treatment are summarized in Table 1 (Example) and Table 2 (Comparative Example).

[0091] In Comparative Example 11, copper foil (FV-WS, thickness: 18 μm) (product of Furukawa Electric Co., Ltd.) was used, whereas in the Examples and other Comparative Examples, electrolytic copper foil satisfying Rz 0.3 μm or less and rolled copper foil satisfying Rz 0.6 μm or less were used. The LCP was used as the laminating surface, and the electrolytic copper foil used the shiny side (glossy side; a flat side compared to the opposite side). Additionally, since there is no difference in the surface shape of the rolled copper foil depending on the side, one side was used. Multiple test specimens were prepared for the copper foils of the Examples and Comparative Examples under the same conditions. Furthermore, the copper foil of Comparative Example 11 was not subjected to any of the following treatments.

[0092]

[0093]

[0094] (1-1) Oxidation treatment

[0095] Copper foil was immersed in the oxidizing agents shown in Tables 1 and 2 under the conditions shown in Tables 1 and 2 to perform oxidation treatment on both sides of the copper foil. After oxidation treatment, the copper foil was washed with water and then dried.

[0096] (1-2) Electroplating Treatment

[0097] For the copper foil after oxidation treatment, double-sided electroplating was performed under the conditions shown in Tables 1 and 2. After the electroplating treatment, the copper foil was washed with water and then dried.

[0098] (1-3) Coupling Process

[0099] For the copper foil after plating, it was immersed in the silane coupling agent solution described in Tables 1 and 2, and then heat-treated under the conditions shown in Tables 1 and 2.

[0100] (1-4) Lamination with LCP

[0101] For Vecstar CT-Q film (LCP) (product of Kuraray Co., Ltd., thickness 50 μm), a vacuum press was used to heat the film at 0 MPa until it reached 260°C and maintained at 260°C for 15 minutes. Then, the film was pressurized at 4 MPa and heated until it reached 320°C, and maintained at 320°C for 10 minutes. After that, the film was cooled while maintaining the pressurization at 4 MPa.

[0102] For the Bexstar CT-Z film (LCP) (manufactured by Kurare Co., Ltd., thickness 50 μm), a vacuum press was used to heat the film at 0 MPa until it reached 260°C and maintained at 260°C for 15 minutes. Then, the film was pressurized at 4 MPa and heated until it reached 300°C, and maintained at 300°C for 10 minutes. After that, the film was cooled while maintaining the pressurization at 4 MPa.

[0103] (4) Evaluation method of copper foil

[0104] Figure 1 shows a scanning electron microscope (SEM) image of a representative surface of the obtained copper foil.

[0105] (4-1) Amount of Ni attached

[0106] For each test specimen, the amount of Ni deposited was measured. First, a copper piece was dissolved in 12% nitric acid, and the resulting liquid was analyzed using an ICP emission analyzer 5100 SVDV ICP-OES (product of Agilent Technologies, Inc.) to measure the concentration of Ni and calculate the amount of Ni deposited per surface area.

[0107] (4-2) Ra, Rz, RSm

[0108] For each test specimen, a contour curve was created from the observation results using a confocal microscope OPTELICS H1200 (manufactured by Lasertec Corporation), and Ra, Rz, and RSm were calculated according to the method specified in JIS B 0601:2001. As measurement conditions, the scan width was set to 100 μm, the scan type to area, the light source to blue, and the cut-off value to 1 / 5. The object lens was set to x100, the contact lens to x14, the digital zoom to x1, and the Z-pitch to 10 nm, and data was acquired from three locations, and Rz was taken as the average value of the three locations.

[0109] (4-3) Area ratio of convex portions in surface images

[0110] A grayscale image of the copper foil surface at a magnification of 50,000x obtained by a scanning electron microscope (SEM) was binarized using WinROOF 2018 (ver. 4.5.5) (MITANI CORPORATION) with a grayscale value of 120 as the threshold, and the area ratio of the convex portion was measured in the binarized image. Examples of images before and after binarization are shown in Figure 2.

[0111] (4-4) Number of intersection points

[0112] When using a scanning electron microscope (SEM) to obtain an image of a cross-section perpendicular to the surface of the copper foil or the interface between the LCP and the copper foil in the laminate, if the distance between two parallel lines passing through the highest and lowest points of the irregularities present on the surface or interface is minimized—that is, if all irregularities fall between the two parallel lines while the distance between the lines is minimized—these lines are considered to be parallel to the surface or interface and are designated as Level 1 and Level 0, respectively (Fig. 3A). Then, a third parallel line corresponding to Level 0.5, which is in the middle of these, is drawn (Fig. 3B), and the number of intersection points between the line and the irregularities is counted (Fig. 3C). Furthermore, a cross-section perpendicular to the surface or interface of the copper foil refers to a cross-section perpendicular to a line using an image with a resolution sufficient to make the surface or interface appear as a straight line.

[0113] (4-5) High-frequency characteristics

[0114] The core material was a Bexstar CT-Z film (LCP) (manufactured by Kurare Co., Ltd., thickness 50 μm) and the cover material was a Bexstar CT-F film (LCP) (manufactured by Kurare Co., Ltd., thickness 25 μm). Using a vacuum press, the film was heated at 0 MPa until it reached 260°C and held at 260°C for 15 minutes. Afterward, it was pressurized at 4 MPa and heated until it reached 300°C, and held at 300°C for 10 minutes. Subsequently, the film was cooled while maintaining the pressure at 4 MPa and heat-pressed to produce a microstrip line with a length of 100 mm. The circuit width was set to 95 μm and the characteristic impedance to 50 Ω. High-frequency signals up to 20 GHz were transmitted through this transmission line using a network analyzer, and the transmission loss was measured.

[0115] (4-6) Peel strength

[0116] The wiring board was fabricated by masking the laminate with a 10 mm wide tape and etching it. Afterwards, the peel strength was measured when the copper foil was peeled from the resin at a speed of 50 mm / min in a 90° direction.

[0117] (5) Evaluation results of copper foil

[0118] The evaluation results are shown in Table 3 (Example) and Table 4 (Comparative Example).

[0119]

[0120]

[0121] (4-1) Amount of Ni attached

[0122] There was no significant difference in this value between the examples and the comparative examples.

[0123] (4-2) Ra, Rz, RSm

[0124] In the examples, Ra was in the range of 0.034 μm to 0.092 μm, Rz was in the range of 0.25 μm to 0.87 μm, and RSm was in the range of 1.21 μm to 3.57 μm. In the comparative examples, there were no test specimens in which all three values ​​were within the aforementioned ranges.

[0125] In addition, when Ra was set to a range of 0.01 μm or more and 0.10 μm or less and RSm was set to a range of 1.20 μm or more and 4.00 μm or less, all of the examples were within the range, but all of the comparative examples' Ra were outside this range.

[0126] In addition, when Rz was set to a range of 0.1 μm or more and 0.90 μm or less and RSm was set to a range of 1.20 μm or more and 4.00 μm or less, all of the examples were within the range, but all of the comparative examples' Rz were outside this range.

[0127] (4-3) Number of intersection points

[0128] As explained above, the number of intersection points measured in the examples was all in the range of 10 to 20 per arbitrary 2.3 μm, but in the comparative examples, most were outside that range.

[0129] (4-4) Area ratio of convex portions in surface images

[0130] When the area ratio of the binarized convex portion was set to a range of 58% or more and 73% or less, all test specimens of the comparative example were outside the range.

[0131] In addition, when the area ratio of the binarized convex portion was set to a range of 58% or more and 81% or less, all of the examples were within that range. Most of the test specimens of the comparative examples were outside the range.

[0132] (4-5) High-frequency characteristics

[0133] High frequency characteristics were evaluated as ○ (good) for -4 dB or more and × (poor) for less than -4 dB.

[0134] (4-6) Peel strength

[0135] In the examples, the peel strength was all 0.61 kgf / cm or higher, but in the comparative examples, the test specimens with high-frequency characteristics were all 0.59 kgf / cm or lower.

[0136] (organize)

[0137] As in Comparative Examples 1, 2, 7, and 8, when the ratio of sodium hypochlorite concentration to alkali is higher than the appropriate amount, the copper foil surface has a needle-like shape with poor affinity for the LCP resin compared to the example, and sufficient peel strength is not obtained.

[0138] As in Comparative Examples 3, 5, and 6, when the alkali concentration is lower than the appropriate level, a shape with high affinity with LCP as in the example cannot be produced on the copper foil surface, and sufficient peel strength is not obtained.

[0139] As in Comparative Examples 4, 10, and 11, when the alkali concentration is higher than the appropriate level, the surface roughness of the copper foil becomes larger than necessary, and good high-frequency characteristics are not obtained.

[0140] As in Comparative Example 9, when the sodium hypochlorite concentration ratio to alkali is appropriate but the sodium hypochlorite concentration is higher than appropriate, the copper foil surface has a needle-like shape with poor affinity for LCP resin compared to the example, and sufficient peel strength is not obtained.

[0141] As in Comparative Example 12, if the plating particles on the surface of the copper foil are too large, good high-frequency characteristics are not obtained.

[0142] In the case of using conventional rough copper foil, it is possible to achieve physical adhesion with LCP through the anchor effect, but transmission loss increases due to the influence of surface effects, and it cannot be said that the requirements for high-frequency characteristics are sufficiently satisfied. In addition, in the case of using conventional low-roughness copper foil, there is a problem with adhesion between LCP and copper foil due to the lack of affinity between LCP and copper foil.

[0143] However, as disclosed in the present disclosure, if a wiring board is manufactured using a resin substrate composed of a copper piece having a combination of Ra, Rz, and RSm as described above and LCP, a wiring board is obtained that can achieve both good high-frequency characteristics and high peel strength.

[0144] Industrial applicability

[0145] According to the present invention, when a wiring board is manufactured using a resin substrate made of LCP, it is possible to provide a copper foil that can achieve both good high-frequency characteristics and high peel strength.

Claims

Claim 1 A laminate having a copper foil laminated on a resin substrate, wherein the copper foil has irregularities on some or all of its surface, and the Ra of the irregularities is 0.01 μm or more and 0.10 μm or less, and the RSm is 1.20 μm or more and 4.00 μm or less. Claim 2 A laminate having a copper foil laminated on a resin substrate, wherein the copper foil has irregularities on a part or all of its surface, and the Rz of the irregularities is 0.2 μm or more and 0.90 μm or less, and the RSm is 1.20 μm or more and 4.00 μm or less. Claim 3 In claim 1 or 2, the copper foil is a laminate in which the Ra of the irregularities is 0.034 μm or more and 0.092 μm or less, the Rz is 0.25 μm or more and 0.87 μm or less, and the RSm is 1.21 μm or more and 3.57 μm or less. Claim 4 A laminate according to claim 1 or 2, wherein the copper foil is a binary image in which the area ratio of the binary convex portion is 42% or more and 90% or less, in a grayscale image obtained by scanning electron microscope (SEM) of the surface at a magnification of 50,000x with a grayscale value of 120 as the threshold. Claim 5 In claim 4, the copper foil is a laminate having an area ratio of 58% or more and 81% or less in a binary image obtained by scanning electron microscope (SEM) of the surface at a magnification of 50,000x, with a grayscale value of 120 as the threshold. Claim 6 In claim 4, the copper foil is a laminate having an area ratio of 58% or more and 73% or less in a binary image obtained by scanning electron microscope (SEM) of the surface at a magnification of 50,000x, with a grayscale value of 120 as the threshold. Claim 7 A laminate according to claim 1 or 2, wherein, in an image by scanning electron microscope (SEM) of a cross-section perpendicular to the surface, the copper foil is a straight line parallel to the surface of the copper foil drawn from the highest and lowest points of the irregularities, designated as Level 1 and Level 0 respectively, and the number of intersection points between the straight line of Level 0.5 and the contour of the surface is 5 or more and 50 or less per any 2.3 μm. Claim 8 In claim 7, the copper foil is a laminate in which, in an image obtained by scanning electron microscope (SEM) of a cross-section perpendicular to the surface, straight lines parallel to the surface of the copper foil are drawn from the highest and lowest points of the irregularities and are designated as Level 1 and Level 0, respectively, such that the number of intersection points between the straight line of Level 0.5 and the contour of the surface is 10 or more and 20 or less per any 2.3 μm. Claim 9 In claim 1 or 2, the copper foil is a laminate in which a first layer containing copper oxide exists on part or all of the surface of the copper foil. Claim 10 In claim 9, the copper foil is a laminate having a second layer containing a metal other than copper on the surface of the first layer. Claim 11 In item 10, the copper foil is a laminate in which the second layer is a plating film. Claim 12 In item 10, the copper foil is a laminate in which a metal other than copper includes nickel. Claim 13 In item 10, the average adhesion amount of the second layer of the copper foil is 0.8 to 6.0 mg / dm 2 Phosphorus, laminate. Claim 14 A laminate having a copper foil laminated on a resin substrate, wherein, in a scanning electron microscope (SEM) image of a cross-section perpendicular to the interface between the resin substrate and the copper foil, a straight line parallel to the interface is drawn from the highest and lowest points of the irregularities present at the interface and designated as Level 1 and Level 0, respectively, and the number of intersection points between the straight line of Level 0.5 and the irregularities is 5 or more and 50 or less per any 2.3 μm. Claim 15 A laminate according to claim 14, wherein the number of the above intersection points is 10 or more and 20 or less per any 2.3 μm. Claim 16 An electronic component equipped with a copper foil having irregularities on some or all of its surface, wherein the Ra of the irregularities is 0.01 μm or more and 0.10 μm or less, and the RSm is 1.20 μm or more and 4.00 μm or less. Claim 17 An electronic component equipped with a copper foil having irregularities on some or all of its surface, wherein the Rz of the irregularities is 0.2 μm or more and 0.90 μm or less, and the RSm is 1.20 μm or more and 4.00 μm or less. Claim 18 Electronic component equipped with a laminate according to Paragraph 14. Claim 19 A method for manufacturing a laminate according to claim 1 or 2, comprising a first step of forming irregularities by treating a copper foil that serves as a material with an oxidizing agent, wherein the oxidizing agent contains a hydroxide of 20 g / L or more and 160 g / L or less. Claim 20 A method for manufacturing a laminate, wherein the hydroxide in paragraph 19 is sodium hydroxide, potassium hydroxide, or a combination thereof. Claim 21 A method for manufacturing a laminate according to claim 19, wherein the oxidizing agent contains 60 g / L or less of hypochlorite. Claim 22 A method for manufacturing a laminate, wherein the chlorite is sodium chlorite, potassium chlorite, or a combination thereof, in paragraph 21. Claim 23 A method for manufacturing a laminate according to claim 21, wherein the ratio of the content of the hypochlorous acid to the content of the hydroxide is greater than 0 and less than or equal to 1.

0. Claim 24 A method for manufacturing a laminate according to claim 19, comprising a second process of treating the copper foil, which is the material, with an alkaline solution with a pH of 9 or higher, which is performed before the first process. Claim 25 A method for manufacturing a laminate according to claim 19, comprising a third process of treating the copper foil with a solvent, which is performed after the first process. Claim 26 A method for manufacturing a laminate according to claim 19, comprising a fourth process of treating the copper foil with a reducing agent, which is performed after the first process. Claim 27 A method for manufacturing a laminate according to claim 19, comprising a fifth process of plating the copper foil, which is performed after the first process. Claim 28 A method for manufacturing a laminate according to claim 19, comprising a sixth process of treating the copper foil with a coupling agent, which is performed after the first process. Claim 29 A method for manufacturing a laminate according to claim 1 or 2, comprising a process of laminating a copper foil onto a resin substrate. Claim 30 A method for manufacturing a laminate according to claim 29, wherein the resin substrate contains a liquid crystal polymer (LCP). Claim 31 delete

Citation Information

Patent Citations

  • Electrode for lithium secondary battery and lithium secondary battery

    JP2002151056A

  • Rolled copper foil for lithium battery collector

    JP2011009207A

  • Copper foil, negative electrode current collector for lithium-ion battery containing the same, and method of manufacturing the same

    JP6726780B1